2013
DOI: 10.5296/jmr.v5i3.3339
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Entrepreneurial Orientation on the Firm Performance through Strategic Flexibility: A Study on the SMEs Cluster in Malang

Abstract: In the globalization era, the competition faced by all companies can not be avoided, as happened to small businesses in the city of Malang. Globalization will lead to the environment becomes increasingly complex and changing. To cope with the ever-changing environment changes, so SMEs need to increase the EO to improve firm performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…Additionally, the finding of Alarape (2013) indicated a significant association between entrepreneurial orientation and performance. The study of study of Arief, et al, (2013) supported the previous findings that entrepreneurial orientation and performance relationship was found to be positive, with a sample of one hundred and forty small and medium enterprises from Malang. Al -Dhaafri and Al -Swidi (2014) in their study on the entrepreneurial orientation and organizational performance: Do enterprise resource planning systems have a mediating role?…”
Section: Discussionsupporting
confidence: 85%
“…Additionally, the finding of Alarape (2013) indicated a significant association between entrepreneurial orientation and performance. The study of study of Arief, et al, (2013) supported the previous findings that entrepreneurial orientation and performance relationship was found to be positive, with a sample of one hundred and forty small and medium enterprises from Malang. Al -Dhaafri and Al -Swidi (2014) in their study on the entrepreneurial orientation and organizational performance: Do enterprise resource planning systems have a mediating role?…”
Section: Discussionsupporting
confidence: 85%
“…However, available empirical findings regarding EO-performance relationship are mixed. Some studies found a positive EO-performance relationship (Arief et al, 2013) while others confirmed a negative EO-performance relationship (Slater & Narver, 2000). Given the inconclusiveness and divergent arguments about EO-performance relationship, the EO-performance relationship needs to be further examined.…”
Section: Entrepreneurial Orientation (Eo) and Organizational Performancementioning
confidence: 99%
“…Contrary to the proposition that entrepreneurial activities within existing organizations contribute to improved organizational performance, extant empirical findings show that the relationship between entrepreneurial orientation and organizational performance is unclear and inconclusive (Rauch, Wiklund, Lumpkin, & Frese, 2009). Some researchers confirmed a positive relationship between entrepreneurial orientation and organizational performance (Arief, Thoyib, Sudiro, & Rohman, 2013;Jia, Wang, Zhao, & Yu, 2014;Karacaoglu, Bayrakdaroglu, & San, 2012;Mahmood & Wahid, 2012;Mokaya, 2012;Sharma & Dave, 2011;Zhang & Zhang, 2012). Others found a negative entrepreneurial orientation-performance relationship (Covin, Slevin, & Schultz, 1994;George, Wood JR, & Khan, 2001;Shamsuddin, Othman, & Shahadan, 2012;Slater & Narver, 2000).…”
mentioning
confidence: 94%
“…Previous studies suggest that firm performance conceptualization suffer from two main problems identified as organizational performance and measurement dilemma [33]. Most of existing studies have widely used business performance and organizational performance concepts interchangeably suggesting that there is no conceptualization differences between the two concepts [24][25][26]34,35].…”
Section: Business Performancementioning
confidence: 99%